2018
DOI: 10.3390/foods7050078
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Treatment of Non-Hydrated Flour Affects Structural Characteristics and Hydration

Abstract: In recent years, high-pressure treatment (HPT) has become an established process concerning the preservation of food. However, studies dealing with the structural, and consequently functional modification of non-hydrated starchy matrices (moisture content ≤ 15%) by HPT are missing. To close this knowledge gap, pressure (0–600 MPa, 10 min) and pressurization time depending (0–20 min, 450 MPa) alterations of wheat flour were investigated. Pressure rise from 0 to 600 MPa or pressurization time rise from 0 to 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…However, there was no significant difference in the amylose content at the same pressure for different pressurization times (15 and 30 min). A similar result was observed by Jakobi, Jekle, and Becker (2018), who found that the amylose content of wheat flour was increased from 31.7% to 40.3% with the pressure increased from 0.1 to 600 MPa. Liu, Wang, Cao, Fan, and Wang (2016) also found that the amylose content of common buckwheat starch was increased from 28.1% at 0.1 MPa to 35.4% at 600 MPa.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, there was no significant difference in the amylose content at the same pressure for different pressurization times (15 and 30 min). A similar result was observed by Jakobi, Jekle, and Becker (2018), who found that the amylose content of wheat flour was increased from 31.7% to 40.3% with the pressure increased from 0.1 to 600 MPa. Liu, Wang, Cao, Fan, and Wang (2016) also found that the amylose content of common buckwheat starch was increased from 28.1% at 0.1 MPa to 35.4% at 600 MPa.…”
Section: Resultssupporting
confidence: 89%
“…Compared to native starches, damaged starch contents of maize, potato, and sweet potato starches were significantly increased with the pressure increasing, which were 10.19%, 7.37%, and 6.98% at 500 MPa for 30 min, respectively. Damaged starch contents were also increased in potato starch treated at 500 MPa (Zhang et al., 2019), barley flour treated at 550 MPa (Ueno et al., 2019), and wheat flour treated at 600 MPa (Jakobi et al., 2018). In addition, maize starch showed higher damaged starch content than those of potato and sweet potato starches at 500 MPa, indicating its higher susceptibility to HHP.…”
Section: Resultsmentioning
confidence: 99%
“…Algunos de los métodos tradicionales de conservación se han mantenido hasta la fecha, debido a que suelen emplear una menor cantidad de energía y dejan una menor huella de carbono; además de permitir la conservación de aspectos como el color, sabor, textura, micronutrientes y valor nutricional (Mukhophadhay et al, 2017;Abera, 2019;Komora et al, 2020). Más recientemente, la preservación de los alimentos, se enfoca en conservar los nutrientes, una apariencia natural y fresca en aquellos alimentos que pasan por un mínimo de procesamiento o que no necesariamente dependen de temperaturas de congelación, se suelen utilizar altas presiones hidrostáticas en combinación con métodos de conservación naturales (Mukhophadhay et al, 2017;Jakobi et al, 2018;Abera, 2019;Komora et al, 2020;Govaris and Pexara, 2021).…”
Section: Tecnologías De La Conservación De Alimentosunclassified
“…En cuanto a las tecnologías acústicas, su utilización requiere de una alta inversión, por ello es de las menos utilizadas; sin embargo, con los avances tecnológicos, algunos componentes reducen sus costos, haciéndola más exequible para su utilización (Mondanese et al, 2018). Las tecnologías biológicas suelen emplear tratamiento de altas presione en combinación con compuestos como películas plásticas (de origen biológico), enzimas, entre otros (Gómez-Estaca et al, 2018;Jakobi et al, 2018). En este caso el tratamiento de altas presiones tiene como resultado la hidrólisis parcial del almidón contenido en los alimentos, lo que altera su composición (Jakobi et al, 2018).…”
Section: Tecnologías Emergentes De La Conservación De Los Alimentosunclassified
“…Although a lot of research was related to physical starch modification in suspensions, as heat moisture treatments (HMT), annealing and ultrasonic treatments [10,11,12,13,14,15], only few studies have dealt with modification techniques, as high-pressure treatment, of cereal materials with low moisture content (≤14%) [16]. Thereby, the type of structural and consequently, functional characteristics of flours strongly depend on the modification technique and the parameters used.…”
Section: Introductionmentioning
confidence: 99%